Surgical hyoid bone repositioning effects on mandibular advancement and upper airway collapsibility: an anesthetized rabbit model study - Tannous, Hiba J.; Samaha, Corine J.; Chami, Hassan A.; Ghafari, Joseph G.; Amatoury, Jason (Frontiers in Physiology, 2025)
BackgroundMandibular advancement serves as a treatment option for obstructive sleep apnea (OSA), but its effectiveness differs among patients. The position of the hyoid bone is crucial for maintaining upper airway patency and may influence mandibular advancement outcomes. This study aimed to assess the impact of surgical hyoid re-positioning on mandibular advancement-induced changes in upper airway collapsibility in an animal model.MethodsTwelve anesthetized male New Zealand White rabbits underwent mandibular advancement (0–4 mm), combined with hyoid repositioning in various directions (anterior, cranial, caudal, anterior-cranial, anterior-caudal) and increments (0–4 mm). Upper airway collapsibility was quantified as the negative pressure required to close the airway (Pclose) at various mandibular and hyoid positions.ResultsIncreasing mandibular advancement alone led to a progressive reduction in Pclose, indicating a decrease in upper airway collapsibility. Similarly, anterior hyoid repositioning alone resulted in incremental reductions in Pclose, with similar outcomes observed for anterior-cranial and anterior-caudal directions. When mandibular advancement was combined with anterior-based hyoid repositioning directions, a further decrease in Pclose was observed compared to when either intervention was applied alone. Cranial and caudal hyoid repositioning had no direct effect on Pclose or on mandibular advancement outcomes.ConclusionIn summary, decreases in upper airway collapsibility induced by mandibular advancement are dependent on both hyoid repositioning direction and increment. The findings suggest that combining mandibular advancement with anterior-based hyoid repositioning may enhance the effectiveness of mandibular advancement in treating OSA.